Nutritional status of pregnant women: prevalence and associated pregnancy outcomes Estado nutricional de gestantes: prevalência e desfechos associados à gravidez - Luciana Bertoldi Nucci; Maria Inês Schmidt; Bruce Bartholow Duncan; Sandra Costa Fuchs; Eni Teresinha Fleck; Maria Margarida Santos Britto (Universidade de São Paulo, 2001)
INTRODUCTION: Although obesity is well recognized as a current public health problem, its prevalence and impact among pregnant women have been less investigated in Brazil. The objective of the study was to evaluate the impact of pre-obesity and obesity among pregnant women, describing its prevalence and risk factors, and their association with adverse pregnancy outcomes. METHODS: A cohort of 5,564 pregnant women, aged 20 years or more, enrolled at aproximately 20 to 28 weeks of pregnancy, seen in prenatal public clinics of six state capitals in Brazil were followed up, between 1991 and 1995. Prepregnancy weight, age, educational level and parity were obtained from a standard questionnaire. Height was measured in duplicate and the interviewer assigned the skin color. Nutritional status was defined using body mass index (BMI), according to World Health Organization (WHO) criteria. Odds ratios and 95% confidence interval were calculated using logistic regression. RESULTS: Age-adjusted prevalences (and 95% CI) based on prepregnancy weight were: underweight 5.7% (5.1%-6.3%), overweight 19.2% (18.1%-20.3%), and obesity 5.5% (4.9%-6.2%). Obesity was more frequently observed in older black women, with a lower educational level and multiparous. Obese women had higher frequencies of gestational diabetes, macrosomia, hypertensive disorders, and lower risk of microsomia. CONCLUSIONS: Overweight nutritional status (obesity and pre-obesity) was seen in 25% of adult pregnant women and it was associated with increased risk for several adverse pregnancy outcomes, such as gestational diabetes and pre-eclampsia. INTRODUÇÃO: A obesidade é um problema atual de saúde pública, com repercussões na gravidez. Pouco se sabe sobre sua prevalência em gestantes brasileiras. Assim, realizou-se estudo com o objetivo de avaliar o impacto da obesidade e da pré-obesidade na gravidez, descrevendo sua prevalência, fatores de risco e sua associação com compl icações da gestação. MÉTODOS: Uma coorte de 5.564 gestantes, com idade maior ou igual a 20 anos, com 20 a 28 semanas de gestação, atendidas em serviços de pré-natal geral do Sistema Único de Saúde em seis capitais brasileiras, foram seguidas entre 1991 e 1995. Medidas de peso pré-gravídico, idade, escolaridade e paridade foram obtidas mediante entrevistas utilizando-se questionário padronizado. A altura foi medida em duplicata, e a cor da pele, descrita pelo entrevistador. O estado nutricional foi estabelecido a partir do índice de massa corporal (IMC), utilizando-se os critérios da Organização Mundial da Saúde. Razão de chances e intervalo de confiança de 95% foram calculados por meio de regressão logística. RESULTADOS: As prevalências (IC95%) ajustadas para idade foram: magreza (IMC<18,5 kg/m²), 5,7% (5,1%-6,3%); pré-obesidade (25<IMC<30 kg/m²), 19,2% (18,1%-20,3%); e obesidade (30<IMC kg/m²), 5,5% (4,9%-6,2%). A obesidade foi mais freqüente em mulheres mais velhas, negras, com menor grau de escolaridade e multíparas. Mulheres obesas apresentaram risco maior para diabetes gestacional, macrossomia, distúrbios hipertensivos, e menor risco para microssomia. CONCLUSÕES: Sobrepeso (pré-obesidade ou obesidade) ocorreu em 25% das gestantes adultas estudadas e associou-se a vários riscos de complicações de gravidez, como diabetes gestacional e pré-eclampsia.